Anticipated BSDEs with reflection in convex region. Issue 3 (3rd April 2023) - Xu, Xiaoyan; Zhang, Mingbo
Abstract : In this paper, we deal with a class of reflected anticipated backward stochastic differential equation with convex reflecting boundary conditions. The existence and uniqueness of solution is obtained for equation with Lipschitz and non-Lipschitz generator respectively.